Democratic Accountability, Deficit Bias, and Independent Fiscal Agencies - Debrun, Xavier (IMF Working Papers; Working Paper, 2011)
Despite growing interest among policymakers, there is no theory of independent fiscal institutions. The emerging literature on "fiscal councils" typically makes informal parallels with the theory of central bank independence, but a very simple formal example shows that such a shortcut is flawed. The paper then illustrates key features of a model of independent fiscal agencies, and in particular the need (1) to incorporate the intrinsically political nature of fiscal policy - which precludes credible delegation of instruments to unelected decisionmakers - and (2) to focus on characterizing "commitment technologies" likely to credibly increase fiscal discipline.